Fire Safety Evaluation and Emergency Planning: An Integrated Risk Reduction Strategy (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The fire safety evaluation is a necessary process in industrial, commercial, and institutional settings to avoid fire-related incidents, protect lives, and reduce property losses. To assess fire hazards and ignition sources and to prevent fire and control systems. This paper gives the methodology of fire safety precaution and prevention in different places like industries, workplaces, and domestic places. This paper analyzes risk assessment, engineering control systems, emergency preparation, and precaution and prevention methods in the chemical industry. By systematic approach in the fire evaluation system in the chemical industry to give training in all zones in the industry, maintenance of equipment, and periodic audits, it is recommended to give a compliance report correctly regarding fire safety and sustainable fire safety permanence.